2020
DOI: 10.1371/journal.pone.0242499
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern of perinatal mortality and its determinants in Ethiopia: Data from Ethiopian Demographic and Health Survey 2016

Abstract: Background The perinatal mortality rate in Ethiopia is among the highest in Sub Saharan Africa. The aim of this study was to identify the spatial patterns and determinants of perinatal mortality in the country using a national representative 2016 Ethiopia Demographic and Health Survey (EDHS) data. Methods The analysis was completed utilizing data from 2016 Ethiopian Demographic and Health Survey. This data captured the information of 5 years preceding the survey period. A total of 7230 women who at delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 59 publications
1
15
0
6
Order By: Relevance
“…Even though joint decision-making with spouses about family planning has significant importance [ 16 ], women are underrepresented in decision-making power on child spacing worldwide [ 17 ]. In Ethiopia, among the top causes of perinatal mortality is pregnancy termination [ 18 ]. The most common reason women mentioned for nonuse of family planning was husband objections [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though joint decision-making with spouses about family planning has significant importance [ 16 ], women are underrepresented in decision-making power on child spacing worldwide [ 17 ]. In Ethiopia, among the top causes of perinatal mortality is pregnancy termination [ 18 ]. The most common reason women mentioned for nonuse of family planning was husband objections [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study in seven East African and seven West African countries found higher neonatal mortality in Ethiopia, Kenya, and Tanzania compared to the rest of the countries [ 23 ]. Studies in Malawi [ 24 ], Nigeria [ 25 ], and Ethiopia [ 26 , 27 ] also found inequalities in perinatal deaths within the countries. For instance, relatively lower perinatal deaths in Ethiopia were found in Addis Ababa, some parts of Tigray, Gambella, Benishangul-Gumuz, and Southern Nations Nationalities and Peoples Region, whereas significantly higher perinatal deaths were recorded in the Somali region, South Amhara, North Oromia, and Southern Afar [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Malawi [ 24 ], Nigeria [ 25 ], and Ethiopia [ 26 , 27 ] also found inequalities in perinatal deaths within the countries. For instance, relatively lower perinatal deaths in Ethiopia were found in Addis Ababa, some parts of Tigray, Gambella, Benishangul-Gumuz, and Southern Nations Nationalities and Peoples Region, whereas significantly higher perinatal deaths were recorded in the Somali region, South Amhara, North Oromia, and Southern Afar [ 26 , 27 ]. For example, in one study, women within a specific hotspot area in the Somali region of Ethiopia had a 22.5 times higher risk of experiencing stillbirth than women outside the hotspot area [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primipara, prematurity, low birth weight, perinatal asphyxia, respiratory distress syndrome, congenital anomalies, neonatal sepsis, and duration of hospital stay increased the deaths (7,8). Maternal age, rural residence, ever terminated pregnancy, and place of delivery were increased perinatal deaths, while husband education, higher wealth index, longer birth interval, female household leader, and the number of antenatal care (ANC) inversely related (12). The under-five mortality showed clustering in the country in Benishangul-Gumuz, Afar, Gambella, and the South Nation Nationality and People (SNNP) Regions until the year 2016 (13).…”
Section: Introductionmentioning
confidence: 99%